Genome-wide identification of DNA-binding with one finger transcription factor genes in Chinese chestnut and their response to abiotic stress - Xu, XiuRong; Jiang, Xibing; Cheng, Shiming (Frontiers in Plant Science, 2025)
DNA-binding with One Finger (Dof) proteins are unique single zinc finger transcription factors that play important roles in plant growth, development, and abiotic stress responses. However, the Dof genes in Chinese chestnut (Castanea mollissima) have not been studied yet. The transcription factor family in the Chinese chestnut genome was identified and analyzed using bioinformatics. The analysis results revealed that a total of 25 CmDof genes (CmDof1 – CmDof25) were identified in Chinese chestnut. Furthermore, we assessed the physicochemical properties, phylogeny, gene structures, cis-regulatory elements (CREs), and expression profiles. The 25 CmDof genes were categorized into five subfamilies according to the phylogeny analysis. Analysis of cis-acting elements revealed that the promoter region of the Dof gene in Chinese chestnut contains light regulation, plant growth and development, plant hormones, and stress-response elements to adapt to environmental changes. The RNA-seq data analysis indicated the potential roles of CmDof genes in the response to temperature stress, drought stress, and shade stress. Additionally, The expression levels of nine CmDof genes showed significant differences in their response to the three abiotic stresses, confirmed by RT-qPCR assays. Collectively, these data lay a foundation for further functional explorations of CmDof genes, especially concerning the possible application of multiple CmDof genes in breeding tolerant plants.